Characterization of entomogen galls from Mato Grosso do Sul, Brazil - Urso-guimarães, Maria Virginia; Castello, Ana Carolina Devides; Kataoka, Eric Yasuo; Koch, Ingrid (Sociedade Brasileira De Entomologia, 2017)
ABSTRACT In this paper we performed a study of occurrence and characterization of entomogen galls from natural vegetation areas in Mato Grosso do Sul. We surveyed natural areas of four biomes from Mato Grosso do Sul State: Pantanal (Corumbá), Atlantic Forest (Bodoquena), Cerrado (Aquidauana), and Chaco (Porto Murtinho). We identified 186 morphotypes of galls in 115 host plant species from 35 families and 73 genera. The richest families were Fabaceae (N = 34), Sapindaceae (N = 24), Bignoniaceae (N = 17), and Myrtaceae (N = 15). Fifty morphotypes of insects (27%) were found in galls of 38 host plants, 78% of which belongs to Diptera, 10% to Hymenoptera, and the other 12% are divided among Hemiptera, Thysanoptera, Coleoptera, and Lepidoptera. In this study, the geographic distribution of gall morphotypes associated to the cecidomyiids Youngomyia pouteriae Maia, 2004, and Trotteria quadridentata Maia, 2004 (Diptera, Cecidomyiidae), and the wasp Mononeuron duguetiae Fischer, 1981 (Hymenoptera, Braconidae, Doryctinae) are expanded to the localities sampled in MS. In addition, four genera and 24 species of plants were recorded for the first time as hosts to entomogen galls. All occurrences of Cecidomyiidae in Mato Grosso do Sul's localities are new records for this family.
Keywords: Atlantic Forest; Cerrado; Chaco; Pantanal; Neotropical region